Activation of matrix metalloproteinase-2 (MMP-2) by supernatant of anaerobic bacteria cultivated from periodontal pockets - Kassara Pattamapun (Chulalongkorn University, 2013)
Thesis (Ph.D.)--Chulalongkorn University, 2002